Some aspets in the electric arc steelmaking production - Karbowniczek , M. (Theory and Practice of Metallurgy, 2025)
The electric arc furnace (EAF) is the initial aggregate and the key point in many carbon steel and in most stainless-steel melting plants. In the article new solutions in construction, technology, operations and control, used in modern steelmaking plant, will be presented. On literature background the results of author’s investigation in electric steelmaking area will be showed. Special attention will be paid on the foaming slag technology used for thermal efficiency increase which means a low cost operation. New elaborated and patented method of stainless-steel slag foaming technology will be described. With slag foaming is connected the optimization procedure concern on minimum the electrical energy consumption and tap-to-tap time. Industrial application in this area will be presented. As a separate chapter the solution in environmental protection during EAF production will be described.